2010
DOI: 10.1016/j.virol.2010.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of gamma secretase blocks HPV infection

Abstract: Human papillomaviruses (HPV) are common sexually transmitted pathogens that in women predispose them to cervical and other anogenital cancers. HPV vaccines can prevent infection by some but not other sexually transmitted HPVs, but are too costly for use in much of the world at greatest risk to HPV-associated cancers. Microbicides provide an inexpensive alternative to vaccines. In a high throughput screen, drugs that inhibit the cellular protein complex known as gamma secretase were identified as potential HPV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 17 publications
4
41
0
Order By: Relevance
“…However, some of the hits-furin, the γ-secretase complex, and the vacuolar ATPase complex (which causes endosome acidification)-were reported by others to be required for HPV infection or are consistent with our prior understanding of this process (17)(18)(19)(20). The identification of these genes validated our screen design and suggested that our findings were relevant to HPV16 infection.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…However, some of the hits-furin, the γ-secretase complex, and the vacuolar ATPase complex (which causes endosome acidification)-were reported by others to be required for HPV infection or are consistent with our prior understanding of this process (17)(18)(19)(20). The identification of these genes validated our screen design and suggested that our findings were relevant to HPV16 infection.…”
Section: Resultssupporting
confidence: 86%
“…HPV is then thought to be transferred to an as-yetunidentified cell-surface receptor, followed by endocytosis and intracellular trafficking (8)(9)(10)(11)(12)(13)(14)(15). Cyclophilin B and the proteases furin and γ-secretase play essential but not clearly understood roles during HPV entry (16)(17)(18)(19). After HPV is internalized, capsid disassembly is initiated in the endosome by acidification (11,15,20).…”
mentioning
confidence: 99%
“…Before we investigated the defect of these mutant PsVs in more detail, we tested whether the mutant viruses follow the same internalization pathway as wt HPV16. To test this, HeLa cells were infected with wt and mutant PsVs in the presence of well-established inhibitors of HPV16 infection targeting CyPs, ␥-secretase, tyrosine kinases, and endosomal acidification and trafficking (38,46,(48)(49)(50)(51)(52)(53)). All mutant PsVs tested displayed the same inhibition profile as wt HPV16 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…HeLa cells were infected with the reassembled particles in the presence of an inhibitor of furin (dec-RVKR-cmk), an inhibitor of ␥ secretase (compound XXI), or with NH 4 Cl. The first two inhibitors inhibit cellular enzymes known to be required for HPV16 PsV infection (38)(39)(40), while NH 4 Cl is a lysosomotropic inhibitor that neutralizes the pH of endosomes and is known to inhibit HPV16 PsV infection (41,42). All inhibitors prevented infection of HeLa cells with particles reassembled in nuclear extracts prepared from 293TT, 293H, or HaCaT cells (Fig.…”
Section: Characterization Of Assembly Reaction Componentsmentioning
confidence: 97%